Analysis Of Students Mastering Speaking And Listening Skill In English Course Using Interactive Learning Multimedia Method In Online Class At Stikom Uyelindo Kupang - Heni Heni (Universitas Cokroaminoto Palopo, 2023)
The outbreak of the covid-19 virus in Indonesia has had major consequences for the world of education, which has issued a government policy through the ministry of education and culture regarding the prohibition of universities from holding lectures in order to break the chain of the spread of the covid-19 virus. One alternative learning method that is considered appropriate to replace face-to-face lectures with lectures held online by the campus as a facilitator of learning media providers as used on the STIKOM Uyelindo Kupang campus is by using zoom meeting media. In English courses, especially in speaking and listening classes, they have difficulty in giving lectures in online lectures. This will result in the level of mastery of students' speaking and listening skills. Therefore, the authors apply interactive multimedia learning methods using English films that are played during lectures. The purpose of this study was to analyze students' abilities in speaking and listening classes using interactive multimedia learning methods held online. The research method used is quantitative using questionnaires distributed by sampling to students related to the learning method by watching movies in English online classes. This method describes an interactive multimedia learning method held online at STIKOM Uyelindo Kupang in English courses (speaking and listening classes), with STIKOM Uyelindo Kupang students as research subjects. With the application of learning methods with interactive multimedia in speaking and listening classes in English courses, students can experience a fun learning process so that they can improve students' speaking and listening skills.